Regulation of piglet T-cell immune responses by thioredoxin peroxidase from Cysticercus cellulosae excretory-secretory antigens - He, Wei; Sun, Xiaoqing; Luo, Bo; Liu, Meichen; Li, Lizhu; Fan, Xianmin; Ye, Jingming; Zhou, Biying (Frontiers in Microbiology, 2022)
Taenia solium (T. solium) cysticercosis is a serious threat to human health and animal husbandry. During parasitization, Cysticercus cellulosae (C. cellulosae) can excrete and secrete antigens that modulate the host’s T-cell immune responses. However, the composition of C. cellulosae excretory-secretory antigens (ESAs) is complex. This study sought to identify the key molecules in C. cellulosae ESAs involved in regulating T-cell immune responses. Thus, we screened for thioredoxin peroxidase (TPx), with the highest differential expression, as the key target by label-free quantification proteomics of C. cellulosae and its ESAs. In addition, we verified whether TPx protein mainly exists in C. cellulosae ESAs. The TPx recombinant protein was prepared by eukaryotic expression, and ESAs were used as the experimental group to further investigate the effect of TPx protein on the immune response of piglet T cells in vitro. TPx protein induced an increase in CD4+ T cells in piglet peripheral blood mononuclear cells (PBMCs), while CD8+ T cells did not change significantly. This resulted in an imbalance in the CD4+/CD8+ T-cell ratio and an increase in CD4+CD25+Foxp3+ Treg cells in the PBMCs. In addition, TPx protein initiated T helper 2 (Th2)-type immune responses by secreting IL-4 and IL-10 and suppressed Th1/Th17-type immune responses. The results showed that ESAs were involved in regulating piglet T-cell immune responses cells. This suggests that TPx protein found in ESAs plays an essential role to help the parasite evade host immune attack. Moreover, this lays a foundation for the subsequent exploration of the mechanism through which TPx protein regulates signaling molecules to influence T-cell differentiation.